Single dose ofloxacin treatment in women with dysuria and frequency - (:unkn) unknown (My University, 1993)
The efficacy of single dose ofloxacin in lower urinary tract infections was investigated in this study. Fifty-one women with complaints of dysuria and frequency were treated with a single dose of 400 mg ofloxacin orally. The results of urinalysis and urine culture which were performed 4-7 days after the administration of the drug were evaluated. Thirty-eight of the 47 evaluable patients (80.85%) were asymptomatic with normal urinalysis and sterile urine, thus cured. The data of the study suggest that single dose ofloxacin may be the first treatment option in the particular group of women with uncomplicated urinary tract infection.